Adhesion, forces and the stability of interfaces - Guttmann, Robin; Hoja, Johannes; Lechner, Christoph; Maurer, Reinhard J.; Sax, Alexander F. (Beilstein Journal of Organic Chemistry, 2019)
Weak molecular interactions (WMI) are responsible for processes such as physisorption; they are essential for the structure and stability of interfaces, and for bulk properties of liquids and molecular crystals. The dispersion interaction is one of the four basic interactions types – electrostatics, induction, dispersion and exchange repulsion – of which all WMIs are composed. The fact that each class of basic interactions covers a wide range explains the large variety of WMIs. To some of them, special names are assigned, such as hydrogen bonding or hydrophobic interactions. In chemistry, these WMIs are frequently used as if they were basic interaction types. For a long time, dispersion was largely ignored in chemistry, attractive intermolecular interactions were nearly exclusively attributed to electrostatic interactions. We discuss the importance of dispersion interactions for the stabilization in systems that are traditionally explained in terms of the “special interactions” mentioned above. System stabilization can be explained by using interaction energies, or by attractive forces between the interacting subsystems; in the case of stabilizing WMIs, one frequently speaks of adhesion energies and adhesive forces. We show that the description of system stability using maximum adhesive forces and the description using adhesion energies are not equivalent. The systems discussed are polyaromatic molecules adsorbed to graphene and carbon nanotubes; dimers of alcohols and amines; cellulose crystals; and alcohols adsorbed onto cellulose surfaces.
Keywords: adhesion energy; adhesive force; dispersion interaction; weak molecular interaction

Chemical Bonding

The Theory of Intermolecular Forces - Stone, A. (Oxford University Press, 2013)

An Introduction to Hydrogen Bonding - Jeffrey, G. A. (Oxford University Press, 1997)

The Nature of the Hydrogen Bond - Gilli, G.; Gilli, P. (Oxford University Press, 2009)

Valence - Coulson, C. A. (Clarendon Press, 1952)

Intermolecular and Surface Forces - Israelachvili, J. N. (Academic Press, 2011)

(untitled) - Hoja, J.; Sax, A. F.; Szalewicz, K. (Chem. – Eur. J., 2014)

(untitled) - Guttmann, R.; Sax, A. F. (ChemistryOpen, 2017)

(untitled) - Kauzmann, W. (Adv. Protein Chem., 1959)

(untitled) - Wolfenden, R.; Lewis, C. A., Jr (J. Theor. Biol., 1976)

(untitled) - Baldwin, R. L. (FEBS Lett., 2013)

(untitled) - Maurer, R. J.; Sax, A. F. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Glanzer, S.; Sax, A. F. (Mol. Phys., 2013)

(untitled) - Lechner, C.; Sax, A. F. (J. Phys. Chem. C, 2014)

Quantics, Rudiments of Quantum Physics - Levy-Leblond, J.-M.; Balibar, F. (North-Holland, 1900)

(untitled) - Lennard-Jones, J. (Adv. Sci., 1954)

(untitled) - Ahlrichs, R. (Theor. Chim. Acta, 1976)

(untitled) - Böhm, H.-J.; Ahlrichs, R. (J. Chem. Phys., 1982)

(untitled) - Stone, A. J. (J. Phys. Chem. A, 2011)

Non-Relativistic QED Theory of the van der Waals Dispersion Interaction - Salam, A. (Springer, 2016)

(untitled) - Zaremba, E.; Kohn, W. (Phys. Rev. B, 1976)

(untitled) - Zaremba, E.; Kohn, W. (Phys. Rev. B, 1977)

(untitled) - Persson, B. N. J.; Apell, P. (Phys. Rev. B, 1983)

The quantum mechanics of many-body systems - Thouless, D. J. (Academic Press, 1972)

A Guide to Feynman Diagrams in the Many-Body Problem - Mattuck, R. D. (McGraw-Hill, 1976)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - Pernal, K.; Podeszwa, R.; Patkowski, K.; Szalewicz, K. (Phys. Rev. Lett., 2009)

(untitled) - Podeszwa, R.; Pernal, K.; Patkowski, K.; Szalewicz, K. (J. Phys. Chem. Lett., 2010)

(untitled) - Seifert, G.; Porezag, D.; Frauenheim, T. (Int. J. Quantum Chem., 1996)

(untitled) - Elstner, M.; Porezag, D.; Jungnickel, G.; Elsner, J.; Haugk, M.; Frauenheim, T.; Suhai, S.; Seifert, G. (Phys. Rev. B, 1998)

(untitled) - Elstner, M.; Hobza, P.; Frauenheim, T.; Suhai, S.; Kaxiras, E. (J. Chem. Phys., 2001)

(untitled) - Stöhr, M.; Michelitsch, G. S.; Tully, J. C.; Reuter, K.; Maurer, R. J. (J. Chem. Phys., 2016)

(untitled) - Tkatchenko, A.; Scheffler, M. (Phys. Rev. Lett., 2009)

(untitled) - Dobson, J. F. (Int. J. Quantum Chem., 2014)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Reilly, A. M.; Tkatchenko, A. (Chem. Sci., 2015)

(untitled) - Hermann, J.; DiStasio, R. A., Jr; Tkatchenko, A. (Chem. Rev., 2017)

(untitled) - Tkatchenko, A.; DiStasio, R. A.; Car, R.; Scheffler, M. (Phys. Rev. Lett., 2012)

(untitled) - Ambrosetti, A.; Reilly, A. M.; DiStasio, R. A., Jr; Tkatchenko, A. (J. Chem. Phys., 2014)

(untitled) - Maurer, R. J.; Ruiz, V. G.; Tkatchenko, A. (J. Chem. Phys., 2015)

(untitled) - Kohn, W. (Phys. Rev. Lett., 1996)

(untitled) - Prodan, E.; Kohn, W. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Lechner, C.; Sax, A. F. (Appl. Surf. Sci., 2017)

(untitled) - Ruedenberg, K. (Rev. Mod. Phys., 1962)

(untitled) - Ruedenberg, K.; Schmidt, M. W. (J. Comput. Chem., 2007)

(untitled) - Ruedenberg, K.; Schmidt, M. W. (J. Phys. Chem. A, 2009)

(untitled) - Bitter, T.; Ruedenberg, K.; Schwarz, W. H. E. (J. Comput. Chem., 2007)

(untitled) - Bitter, T.; Wang, S. G.; Ruedenberg, K.; Schwarz, W. H. E. (Theor. Chem. Acc., 2010)

(untitled) - Schmidt, M. W.; Ivanic, J.; Ruedenberg, K. (J. Chem. Phys., 2014)

The Chemical Bond - Schmidt, M. W.; Ivanic, J.; Ruedenberg, K. (The Physical Origin of Covalent Bonding, 2014)

(untitled) - Jeziorski, B.; Moszynski, R.; Szalewicz, K. (Chem. Rev., 1994)

(untitled) - Misquitta, A. J.; Podeszwa, R.; Jeziorski, B.; Szalewicz, K. (J. Chem. Phys., 2005)

(untitled) - Heßelmann, A.; Jansen, G.; Schütz, M. (J. Chem. Phys., 2005)

(untitled) - Caldeweyher, E.; Bannwarth, C.; Grimme, S. (J. Chem. Phys., 2017)

(untitled) - Becke, A. D.; Johnson, E. R. (J. Chem. Phys., 2007)

(untitled) - Becke, A. D.; Johnson, E. R. (J. Chem. Phys., 2007)

(untitled) - Grimme, S.; Hansen, A.; Brandenburg, J. G.; Bannwarth, C. (Chem. Rev., 2016)

(untitled) - Aradi, B.; Hourahine, B.; Frauenheim, T. (J. Phys. Chem. A, 2007)

(untitled) - Sun, Y.; Wilson, S. R.; Schuster, D. I. (J. Am. Chem. Soc., 2001)

(untitled) - Perepichka, D. F.; Wudl, F.; Wilson, S. R.; Sun, Y.; Schuster, D. I. (J. Mater. Chem., 2004)

Schwerdtfeger, P. Table of experimental and calculated static dipole polarizabilities for the electronic ground states of the neutral elements (in atomic units)

(untitled) - Nakashima, N. (Sci. Technol. Adv. Mater., 2006)

(untitled) - Tomonari, Y.; Murakami, H.; Nakashima, N. (Chem. – Eur. J., 2006)

Statistical Mechanics - Huang, K. (Wiley, 1987)

GESTIS-Stoffdatenbank

Engineering ToolBox

ChemicalBook—Chemical Search Engine

(untitled) - Lee, S. H.; Lee, H.; Pak, H. (Bull. Korean Chem. Soc., 1997)

(untitled) - Lee, S. H.; Lee, S. K. (Bull. Korean Chem. Soc., 1999)

(untitled) - Yoo, C.-D.; Kim, S.-C.; Lee, S.-H. (Bull. Korean Chem. Soc., 2008)

Chemistry of Fossil Fuels and Biofuels - Schobert, H. (Cambridge University Press, 2013)

(untitled) - Nishiyama, Y.; Langan, P.; Chanzy, H. (J. Am. Chem. Soc., 2002)

(untitled) - Nishiyama, Y.; Johnson, G. P.; French, A. D.; Forsyth, V. T.; Langan, P. (Biomacromolecules, 2008)

(untitled) - French, A. D. (Cellulose, 2017)

(untitled) - Maurer, R. J.; Sax, A. F.; Ribitsch, V. (Cellulose, 2013)

(untitled) - Mazeau, K. (Carbohydr. Polym., 2011)

(untitled) - Da Silva Perez, D.; Ruggiero, R.; Morais, L. C.; Machado, A. E. H.; Mazeau, K. (Langmuir, 2004)

(untitled) - Hoja, J.; Maurer, R. J.; Sax, A. F. (J. Phys. Chem. B, 2014)

Enzyclopedia of Tribology - Wang, Q. J.; Chung, Y.-W. (Springer, 2013)

Coefficients of Friction